2014
DOI: 10.1016/j.eurpsy.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Sustained antipsychotic effect of metacognitive training in psychosis: A randomized-controlled study

Abstract: Persistent psychotic symptoms represent a major challenge for psychiatric care. Basic research has shown that psychotic symptoms are associated with cognitive biases. Metacognitive training (MCT) aims at helping patients to become aware of these biases and to improve problem-solving. Fifty-two participants fulfilling diagnostic criteria of schizophrenia or schizoaffective disorders and persistent delusions and stabilized antipsychotic medication were enrolled in this study. Following baseline assessment patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 53 publications
7
35
3
4
Order By: Relevance
“…The effects of MCT on particular symptom severity, especially delusions, may be considered lower than those obtained from some of the previous studies that were conducted among younger patients (Balzan et al, 2015;Favrod et al, 2014;Moritz et al, 2013). Still, the effects of MCT in our sample were in the range of the results of other studies that had been conducted among younger patients (Aghotor et al, 2010;Moritz, Kerstan, et al, 2011); however, it should be noted that our results are statistically insignificant.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…The effects of MCT on particular symptom severity, especially delusions, may be considered lower than those obtained from some of the previous studies that were conducted among younger patients (Balzan et al, 2015;Favrod et al, 2014;Moritz et al, 2013). Still, the effects of MCT in our sample were in the range of the results of other studies that had been conducted among younger patients (Aghotor et al, 2010;Moritz, Kerstan, et al, 2011); however, it should be noted that our results are statistically insignificant.…”
Section: Discussioncontrasting
confidence: 79%
“…A number of studies have shown that MCT significantly reduces cognitive biases and improves positive symptoms (Aghotor, Pfueller, Moritz, Weisbrod, & Roesch-Ely, 2010;Balzan, Delfabbro, Galletly, & Woodward, 2015;Favrod et al, 2014; for a review see: Moritz, Kerstan, et al, 2011;Moritz, Veckenstedt et al, 2014;Moritz et al, 2013;Moritz, Veckenstedt, Randjbar, Vitzthum, & Woodward, 2011), with only one exception to date (van Oosterhout et al, 2014). Some studies have also shown that MCT increases clinical insight among patients with schizophrenia (Favrod et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is probable that this inconsistency is due to selective floor effects in the MCT+ group: As shown in Tables 1 and 2, the randomization process resulted in differences between the two groups regarding baseline symptoms, which were lower in MCT+ patients -and, in fact, lower than in previous studies by our group (Moritz et al, 2013a;Moritz et al, 2011) and others (Favrod et al, 2014;So et al, 2015). This, in combination with the rapid improvement, led to very low symptom levels in these patients post-intervention, while the control group may have benefited from greater margins for change.…”
Section: Discussioncontrasting
confidence: 38%
“…It has been suggested, though, that delusions are underpinned, at least in part, by a general susceptibility to forming false beliefs/memories with a high level of confidence (Laws and Bhatt, 2005;. Therefore, investigating the factors influencing confidence in false memories could be of high clinical relevance by improving an understanding of the development and maintenance of delusions, and by potentially influencing individual treatment options for schizophrenia (Favrod et al, 2014; for a review, see Moritz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%